Contracting parties or signatories to treaties administered by WIPO, members of the WIPO assemblies and other bodies and committees, members of the International Union for the Protection of New Varieties of Plants (UPOV) : status on April 15, 2011 (WIPO GenevaCH, 2011)
Provides listings of the membership of the various bodies, together with date of membership or date on which Member State became party to the specific convention.
Keywords: WIPO